Analisa Perbandingan Kinerja Keuangan Sebelum Dan Pada Saat Covid-19 Sub Sektor Aneka Industri Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2021 - Nurul Farahdila Putri; Jeni Susyanti; Restu Millaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This research is entitled "Comparative Analysis of Financial Performance before and during Covid-19, Various Industry Sub-Sectors Listed on the Indonesia Stock Exchange in 2018-2021". The purpose of this research is to identify whether there is a difference between Covid-19 and the financial performance of various industrial sectors listed on the Indonesia Stock Exchange before and at the time of Covid-19. The independent variable in this research is the impact of Covid-19. While the dependent variable is financial performance in the form of liquidity, solvency, profitability, and activity. This research uses a quantitative approach, namely by describing or illustrating the data that has been collected and with secondary data as a source of data obtained from the annual financial reports of various industrial companies listed on the Indonesia Stock Exchange 2018-2021. The method of analysis in this research is descriptive statistical test and Wilcoxon signed rank test. The results of this research show that (1) The results of the comparison of Liquidity Ratios and Leverage Ratios before and during Covid-19 for various industrial companies listed on the Indonesia Stock Exchange in 2018-2021 showed no significant difference, (2) Comparison of Profitability Ratios and the activity ratio before and during Covid-19 in various industrial companies listed on the Indonesia Stock Exchange in 2018-2021 there was a significant difference. Keywords: Liquidity, Solvency, Profitability, Activity